Bioactive triterpenoids from the leaves of Eriobotrya japonica as the natural PDE4 inhibitors. Issue 24 (17th December 2017) - Tan, Bing-Xin; Yang, Lu; Huang, Yi-You; Chen, Yun-Yun; Peng, Guang-Tian; Yu, Si; Wu, Yi-Nuo; Luo, Hai-Bin; He, Xi-Xin
Abstract: The ethanolic extract of the leaves of Eriobotrya japonica exhibited inhibitory activity against phosphodiesterase-4D (PDE4D), which is a therapeutic target of inflammatory disease. Subsequent bioassay-guided fractionation led to the isolation of a new triterpene (1 ), together with seven known triterpenoids, methyl corosolate (2 ), ursolic acid (3 ), oleanolic acid (4 ), methyl maslinate (5 ), α -amyin (6 ), 3 β, 19 α, 23-trihydroxy-urs-12-ene (7 ) and uvaol (8 ). The structure of compound1 was established as 3 β -hydroxyl-21 β -acetoxyl-urs-12-en-28-carboxylate on the basis of interpretation of its 1D and 2D NMR and HR-ESI-MS spectroscopic data. The bioassay results verified compounds2, 3 and8 inhibited PDE4D2 effectively with the IC50 values of 3.06, 2.18 and 5.17 μM, respectively, which may provide a novel mechanism for the anti-inflammatory activity of the leaves of E. japonica. Abstract :